Contelações de Sinais Casadas a Grupos Não-Comutativos10.14209/jcis.1999.12 - de Andrade e Silva, Antonio; Palazzo Jr., Reginaldo (Journal of Communication and Information Systems, 2015)
In this paper we consider signal constellations matched to noncommutative groups. These groups are characterized as the semidirect product of a commutative group by a cyclic group of order even. As a consequence, we propose an algorithm to determine the signal constellations matched to such groups.